164k views
1 vote
Khan academyyyy ⠀⠀⠀⠀⠀⠀⠀⠀

Khan academyyyy ⠀⠀⠀⠀⠀⠀⠀⠀-example-1
User Tpow
by
6.3k points

2 Answers

6 votes

Answer:

A

C

E

Explanation:

-4 + (4 + 5)

Using BEDMAS

Brackets

Exponents

Division

Multiplication

Addition

Subtraction

solve brackets first...

(4 + 5) = 9

9 - 4 = 5

A) (-4+4) + 5

= (0) + 5

= 5

B) (-4 - 4) + 5

=(-8) + 5

= - 3

C) -( 4 - 4) + 5

= -(0) + 5

= 5

D) - (4)+ ( -4) + 5

= -4 + -4 + 5

= -8 + 5

= -3

E) -4 + 4 + 5

= 0 + 5

= 5

User Jazzbpn
by
5.7k points
3 votes

Answer:

option A, C , E

Explanation:

- 4 + ( 4 + 5 ) = ( - 4 + 4 ) + 5 [ associative property ]

User Avi Tevet
by
6.7k points